Inborn Metabolic Diseases Diagnosis and Treatment - Fernandes, J;Ed. Saudubray, J M;Ed. Berghe, G Van Den;Ed (Springer, 2000)
The diagnosis and treatment of metabolic diseases represent the main issues of this clinical book. Each disease-related chapter starts with a figure which presents an outline of the metabolic pathway, the locations of its inborn defects, and a short explanation of its major functions. The position of the figure on the left hand page facilitates its consultation when reading the text further. A short clinical abstract on the title page of the chapter is followed by the headings clinical presentation, metabolic derangement, diagnostis (and diagnostic tests), treatment and prognosis, genetics (main abnormalities only) and references, in a fixed order. As to treatment, this involves emergency treatment, maintenance treatment and, if applicable, treatment in the adult. Five chapters on general principles of diagnosis and treatment precede the chapters on specific disorders. The first is the most important chapter, since it is an introduction to the clinical approach to inborn metabolic disease (see Preface). The others deal with diagnostic, procedures, emergency treatment, psychosocial care, and, last but not least, the present status of treatments, with comprehensive lists, as well as new trends of treatment.